Fluid Mechanics of the Downcomer in Circulating Fluidized Beds - Wirth, Karl-Ernst (Preprints Fluidization VIII, 1995)
A fluid mechanical model of segregated vertical gas-solids flow has been developed. Mass and force balances were set up with the aid of this model and, finally, a dimensionless state and pressure drop diagram was calculated. In this diagram, the pressure gradient caused by the solids transport is plotted in dimensionaless form versus the superficial gas velocity in the form of a particle Froude number. Parameter is the ratio of the solids volumetric flow rate at minimum fluidization to the gas volumetric flow rate. The state and pressure drop diagram is valid for a given gas-solids system, i.e. for a given Archimedes number and given minimum fluidization porosity. The fluid mechanical behaviour of different types of circulating fluidized beds can be explained with the aid of the state and pressure drop diagram for segregated vertical gas-solids flow. As an example, the operating behaviour of circulating fluidized bed with a syphon in the solids downcomer is discussed. Measurements of the circulating solids mass flow rates are compared with calculation results.
UnivIS-Import:2015-04-16:Pub.1995.tech.ITC.mechve.fluidm_91
Keywords: fluidization